1972
DOI: 10.1159/000152537
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Studies of Red Cell Enzyme Polymorphisms in Four Spanish Populations

Abstract: In four different popula tions of Spain, the Basques, the Galicians, the Andalusians and in the population of Central Meseta, the genefrequencies of the following geneticmarkers in red cells have been determined and compared: acid phosphatase, adenylate kinase, adenosine deaminase, phosphoglucomutase (locus 1) and 6-phosphogluconate dehydrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
(6 reference statements)
4
11
0
Order By: Relevance
“…19817 Moral et al, 19868 Ribo etal., 19869 Moral etal., 198510 Moral, 198611 M. de Pancorbo,198212 Martell et al, 1986 ards are shown in table 3. The values of ACP*A and ACP*B alleles found in this study are within the range of variation in the Basque populations previously stud ied, but the comparison with the yj test produced some significant differences with Basques [Goedde et al, 1972] and Biscayans [Iturrioz et al, 1983]. The heter ogeneity detected was caused by the lower values of allele ACP*C in our sample which, together with the Arratia popula tion [M. de Pancorbo et al, 1986], is the lowest value described in Basques.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…19817 Moral et al, 19868 Ribo etal., 19869 Moral etal., 198510 Moral, 198611 M. de Pancorbo,198212 Martell et al, 1986 ards are shown in table 3. The values of ACP*A and ACP*B alleles found in this study are within the range of variation in the Basque populations previously stud ied, but the comparison with the yj test produced some significant differences with Basques [Goedde et al, 1972] and Biscayans [Iturrioz et al, 1983]. The heter ogeneity detected was caused by the lower values of allele ACP*C in our sample which, together with the Arratia popula tion [M. de Pancorbo et al, 1986], is the lowest value described in Basques.…”
Section: Resultssupporting
confidence: 81%
“…1 Goedde et al, 19722 Vergnesetah, 1980a3 Iturrioz et ah, 19834 M. de Pancorbo et ah, 19865 Carracedo and Concheiro, 19826 Moreno and Moral. 19817 Ribo et ah, 19868 Moral et ah, 19869 Martell et ah, 1986 ing to the birth place of their grandparents.…”
Section: Introductionmentioning
confidence: 99%
“…As for their genetic structure, the existence of a certain degree of genetic heterogeneity within the Basques has been suggested since the first population-based genetic analyses were performed (Goedde et al 1972(Goedde et al , 1973. On the one hand, some authors have claimed a lack of genetic substructure among the Basques based on investigations using both classical markers (Calafell and Bertranpetit 1994) and HLA genetic markers (Comas et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The Ibiza pop ulation, as well as those of the other Balea ric islands [Miguel, 1988;Moral, 1986], ex hibits frequencies for ACPI*A similar to those published for the Basque country (north Spain) [Martinez de Pancorbo, 1982;Aguirre, 1987] and other Mediterra nean populations [Tsiakalos et al, 1981;Bonne-Tamir et al, 1978;Tills et al, 1983]. However, they differ from those reported from central and southern Spain [Goedde et al, 1972] and from central and northern European populations, which are charac terized by higher frequencies of this allele.…”
Section: Resultsmentioning
confidence: 51%